Tax knowledge and tax compliance of the small and medium enterprises in Vietnam - Hien, Nguyen Thi Thu; Thao, Bui Thi Thu; Tuan, Dang Anh (International Journal of Innovative Research and Scientific Studies, 2025)
This research explored the motivations, behaviors, and consequences of tax non-compliance and aimed to provide empirical evidence to evaluate the impact of tax knowledge, perceived non-tax opportunity and felt tax loss on tax compliance in small and medium enterprises (SMEs). A quantitative approach on a panel of 326 SMEs through SEM linear structural model analysis using SmartPLS software. The hypotheses were tested in a parallel mediation model. The perceived non-tax opportunity and felt tax loss, in contrast to tax knowledge, negatively affect taxpayers’ behavior and tax-compliance level. The two mediators, i.e., perceived non-tax opportunity and felt tax loss, create an indirect relationship between tax knowledge and tax compliance. Without the two mediators, there is no relationship between tax knowledge and tax compliance. The study also added evidence in supporting the view that tax compliance behavior depends on both personal (economic) and social motivations. Furthermore, in the disadvantage case, prospect theory is more suitable to explain tax non-compliance behavior than deterrence theory and vice versa.